The Leader in You: How to Win Friends, Influence People and Succeed in a Changing World
For nearly a century, the words and works of Dale Carnegie & Associates, Inc., have translated into proven success -- a claim verified by millions of satisfied graduates; a perpetual 3,000-plus enrollment roster per week; and book sales, including the mega-bestseller How to Win Friends and Influence People, totaling over thirty million copies.Now, in The Leader In You, coauthors Stuart R. Levine and Michael A. Crom apply the famed organization\'s time-tested human relations principles to demonstrate how anyone, regardless of his or her job, can harness creativity and enthusiasm to work more productively -- 1990s style.